Armed groups the 21st century threat - Thompson, Peter G. (Rowman & Littlefield Publishers, 2014)
In this age of asymmetric warfare, battles are fought more and more against armed groups of opponents such as terrorists, insurgents, or transnational criminal organizations. This text is the first to categorize armed groups and analyze their characteristics in a systematic way to provide a thorough overview of all types of armed groups and the role they play in today's security environment. Drawing on international case studies and histories, the work analyzes the objectives, strategies, and internal composition of armed groups and the environments that foster them. It demonstrates that armed groups often behave in an "hybrid" fashion, be it the criminal actions terrorists groups take to fund their goals or the role terrorist actions play in criminal organizations. As such dividing lines blur, governments need to figure out how, where, and when these armed groups are operating in zones of conflict or peace, as well as their motivations, structures, and ultimate objectives. This thorough and groundbreaking study will provide students with a strategic view of who armed groups are, how to analyze them, and what geopolitical and geostrategic factors influence their origins and operations.